Strengthening Vocational Learning through Teaching Factory Implementation in Visual Communication Design - Khair, Indratni; Astuti, Sri (Universitas Islam Negeri Raden Fatah Palembang, South Sumatra, Indonesia, 2025)
This study aimed to describe the implementation of the Teaching Factory (TEFA) learning model in Vocational High Schools (SMK), especially in the Visual Communication Design Study Program, using descriptive qualitative methods and purposive sampling techniques. Data were collected through observation, interviews, and documentation. Teaching Factory (TEFA) learning model is designed to integrate teaching and learning activities with real production processes in order to provide practical work experience to students through a production-based approach. The results of the study indicated that TEFA learning at SMK Al-Falah consists of seven systematic steps, namely: implementing design briefs, receiving orders, analyzing orders, stating order readiness, working on orders, conducting quality control, and submitting orders. One prominent characteristic is the